Evaluation of cytological radiation damage to lymphocytes after I-131 metaiodobenzylguanidine therapy by the cytokinesis-blocked micronucleus assay - Watanabe, Naoto; Yokoyama, Kunihiko; Kinuya, Seigo; Tonami, Hisao (Annals of Nuclear Medicine, 2016)
Objective The purpose of this study was to evaluate the degree of cytological radiation damage to lymphocytes occurring after I-131 metaiodobenzylguanidine (MIBG) therapy as determined by the cytokinesis-blocked micronucleus assay. The chromosomal damage to lymphocytes induced by I-131 in vivo should result in augmentation of the number of cells with micronuclei. Methods We studied 15 patients with pheochromocytoma (14/15) or ganglioneuroma (1/15), who were treated initially with 7.4 GBq of I-131-MIBG. Isolated lymphocytes collected from patients 10 days after the therapy were harvested and treated according to the cytokinesis-blocked method of Fenech and Morley. Serial blood samples were obtained periodically only from two patients for 2 years after therapy. Micronucleus number of micronuclei per 500 binucleated cells was scored by visual inspection. As controls, lymphocytes from the same patients before the therapy were also studied. In an in vitro study, lymphocytes from eight normal volunteers were exposed to doses varying from 0.5 to 2 Gy and studied with the same method. Results The mean number (mean ± SD) of micronuclei after treatment was significantly increased ( p < 0.001) as compared to control subjects (49.4 ± 8.2 vs. 11.3 ± 6.4). Internal radiation absorbed doses estimated for the 15 patients were 1.6 ± 0.3 Gy in this external irradiation study. The frequency of micronuclei post-administration of I-131-MIBG gradually decreased to near baseline (i.e., pre-therapy) levels by 2 years. Conclusions The relatively low frequency of lymphocyte micronuclei induced by I-131-MIBG in vivo and reversal of the increasing frequency of lymphocyte micronuclei after therapy suggest that the short-term non-stochastic damage induced by this therapy with 7.4 GBq of I-131-MIBG in pheochromocytoma or ganglioneuroma patients is limited and reversible.